2001
DOI: 10.2307/2655419
|View full text |Cite
|
Sign up to set email alerts
|

Why Americans Hate Welfare: Race, Media, and the Politics of Antipoverty Policy

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.235.251.160 on Thu,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(139 citation statements)
references
References 0 publications
3
133
0
3
Order By: Relevance
“…For example, an influential body of literature on racial priming (e.g. Gilens, 1999;Mendelberg, 2001) has demonstrated that racialized cues in mass communications, such as political campaigns and media content, increase the salience of racial attitudes in the evaluation of specific candidates or policies. Exposure to implicit racial cues, such as racially coded phrases like inner city or gang violence, has a strong and significant effect on support for more punitive political candidates and policies, particularly among individuals who are White, less educated, more politically conservative, and harbor greater racial animus toward Black persons (Domke, 2001;Huber and Lapinski, 2006;Peffley and Hurwitz, 2010;White, 2007).…”
Section: Black Criminality Racial Resentment and Primingmentioning
confidence: 99%
“…For example, an influential body of literature on racial priming (e.g. Gilens, 1999;Mendelberg, 2001) has demonstrated that racialized cues in mass communications, such as political campaigns and media content, increase the salience of racial attitudes in the evaluation of specific candidates or policies. Exposure to implicit racial cues, such as racially coded phrases like inner city or gang violence, has a strong and significant effect on support for more punitive political candidates and policies, particularly among individuals who are White, less educated, more politically conservative, and harbor greater racial animus toward Black persons (Domke, 2001;Huber and Lapinski, 2006;Peffley and Hurwitz, 2010;White, 2007).…”
Section: Black Criminality Racial Resentment and Primingmentioning
confidence: 99%
“…Incorporating groups into American Life -moving from the slums into the suburbsmimics Park's race relation cycle. Today, the minority communities are less desirable for various reasons (Chavez, 2008;Da´vila, 2004;Gilens, 2000). The Black community was not the only exception to the race relation cycle, but their undesirability was more pronounced based on phenotype.…”
Section: The Ghetto and The Black Beltmentioning
confidence: 99%
“…This linkage pathologised communities of colour and primarily affected African American and Latino communities. Within the larger discourse, the underclass's utilisation was synonymous with those living under the poverty line, which most often was viewed as Black and Latino as represented by the culture industry (Gilens, 2000).…”
Section: The Genealogy Of the Underclassmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to assume that Black individuals who use drugs and resemble these racial drug stereotypes will be perceived as more likely to have a SUD and more deserving of punishment when compared to White individuals who use drugs. In addition, receiving welfare likely contributes to an interaction of female with receiving welfare, such as a "welfare queen" stereotype (Gilens, 1996(Gilens, , 1999Gilman, 2013;Hancock, 2004). Moreover, the opioid epidemic has contributed to the drug stereotype of a White person who uses opioids, which may elicit more sympathetic perceptions of SUD and less punitive judgements relative to a Black person who uses opioids.…”
Section: Race Drug Stereotypes and Drug Enforcement In The United Statesmentioning
confidence: 99%